Human platelets express and are activated by galectin-8 - Romaniuk, María Albertina (2010)
Gals (galectins) are proteins with glycan affinity that are emerging as mediators of atherosclerosis. Despite the similarities in structure and sequence, different Gals exert distinct effects on their target cells. We have shown that Gal-1 triggers platelet activation, suggesting a role for Gals in thrombus formation. Since Gal-8 is expressed upon endothelial activation and also contributes to inflammation, to understand further the role of these lectins in haemostasis, we evaluated the effect of Gal-8 on human platelets. Gal-8 bound specific glycans in the platelet membrane and triggered spreading, calcium mobilization and fibrinogen binding. It also promoted aggregation, thromboxane generation, P-selectin expression and granule secretion. GP (glycoprotein) αIIb and Ib-V were identified as putative Gal-8 counter-receptors by MS. Studies performed using platelets from Glanzmann?s thromboasthenia and Bernard?Soulier syndrome patients confirmed that GPIb is essential for transducing Gal-8 signalling. Accordingly, Src, PLC2γ (phospholipase C2γ ), ERK (extracellular-signal- regulated kinase) and PI3K (phosphoinositide 3-kinase)/Akt downstream molecules were involved in the Gal-8 signalling pathway. Gal-8 fragments containing either the N- or C-terminal carbohydrate-recognition domains showed that activation is exerted through the N-terminus. Western blotting and cytometry showed that platelets not only contain Gal-8, but also expose Gal- 8 after thrombin activation. These findings reveal Gal-8 as a potent platelet activator, supporting a role for this lectin in thrombosis and inflammation.